Kontribusi Pondok Pesantren terhadap Pengembangan Ekonomi Lokal : Studi di Al-Amanah 2 Mojokrapak - Nanda Prayoga; Davit Amir Dzulqurnain; Deden Adi Hidayat (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Islamic boarding schools not only act as centers of religious education, but also as agents of community economic movement. This study examines the role of Al-Amanah 2 Islamic Boarding School, Mojokrapak, Jombang in strengthening the economy of the surrounding community through a qualitative descriptive approach. Data were collected through observation, in-depth interviews with caregivers, administrators, and the community, as well as document analysis. The results of the study revealed that the Islamic boarding school succeeded in creating jobs, facilitating small community businesses, and building economic synergy between students and local business actors. Business units such as minimarkets, canteens, and local product exhibitions are real evidence of the contribution of Islamic boarding schools in increasing community income. SWOT analysis shows that Islamic boarding schools have great potential to develop a community-based economy, despite facing challenges such as lack of product innovation and market competition. This study concludes that Al-Amanah 2 Islamic Boarding School has become a catalyst for local economic development through a collaborative approach and empowerment based on Islamic values. The recommendation of this study is to strengthen entrepreneurship training programs and develop a wider market network to ensure the sustainability of community economic empowerment.